SISTEM PENGENDALIAN INTERN DAN PENILAIAN ATAS PERSEDIAAN PADA PT HARMONI MITRA UTAMA CABANG SAMARINDA - -, Juara Pakpahan (EKONOMIA, 2014)
This study aims to get a clear picture of the application of internal control systemÂ has applied the company, as well as determine whether the FIFO method is applied to companies generate higher gross profit than the LIFO method and Average method. The author conducted an analysis of inventory systems and procedures PT. Harmoni Mitra Utama Samarinda branch used the comparative method comparative analysis, and attach the form of questionnaires interview process, and to determine the value of ending inventory will affect the gross profit to be received by the PT. Harmoni Mitra Utama, then the cards are used inventory under FIFO, LIFO, and average. Result of the study mentions that the systems and procedures in PT Harmoni MItra Utama has met a good internal control system is supported by the results of questionnaires of 30 items questions, answered 27 items, 27/30 x 100% = 90%, and an assessment of inventory under FIFO produces higher gross profit as compared with LIFO and Average.